Rare earth and trace elements in soil-plant system irrigated with treated wastewater in an arid environment. (2015) - Semhi, Khadija; Abdalla, Osman
The impact of treated wastewater (TWW) used for irrigation of different plants in arid area has been investigated. Different soil samples and plants of several species were collected and analysed for major and trace elements including rare earth elements (REEs). As the concentration of trace elements in TWW is higher than in tap water (TW) (though within the permissible limits for irrigation) their concentration increases in the soil profile under TWW irrigation. Nonetheless trace elements' uptake by plants varies with plant type and therefore it is recommended to asses plant's ability to uptake trace elements prior to implementation of TWW for irrigation although the soil under irrigation with TWW has indicated a slight enrichment in heavy REEs (HREEs), no fractionation of REEs could be indicated for all different plant species. It can be concluded that irrigation with TWW has no impact on the fractionation of REEs by plants; however the distribution of trace elements in plants seems to be more dependent on plant species than on the type of water used for irrigation.